State of the planet. (28th June 2019) - Brenner, Logan
Abstract: Earth is a dynamic planet, with warm and cool periods comprising its detailed climate history. We can find sudden shifts between these phases in the past; however, from the geological time scale perspective, for a transition to be abrupt, it occurs over millennia. In modern times, we are faced with a much faster rate of change, at least an order of magnitude faster than the transition from the last glacial period, about 20, 000 years ago. Modern temperature rise is also accompanied by rising greenhouse gases, which are major contributors to climate change. Atmospheric CO2, a major greenhouse gas, is increasing about 100 times faster than it did during the last deglaciation. This CO2 input can be traced back to human activities and is a necessary piece to the global warming puzzle. The following details the current state of climate on Earth as well as some projections for future conditions. With the scientific outline of our changing climate, we can better understand our roles as contributors and individual and collective responsibility to mitigate these impacts.